Peran Kader Posyandu dalam Meningkatkan Kualitas Pelayanan Kesehatan Ibu Hamil di Desa Kupang, Kabupaten Sidoarjo - Adellia Eka Wandira; Lailul Mursyidah (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The purpose of this study was to examine how Posyandu cadres contribute to improving maternal health services in Kupang Village, Sidoarjo Regency. The qualitative approach used included observation, interviews, and documentation with purposively selected informants. Soekanto's (2001) Role Theory, which encompasses active, passive, and participatory roles, served as the basis for this analysis. The results indicate that cadres have actively participated in data collection and mentoring pregnant women, but they have failed to master 25 basic skills, resulting in an ineffective rotation system. While participatory roles emerged in collaboration with the village government through the "bantras" program, this has not been optimal due to a lack of active cadres and training, and senior cadres are reluctant to be replaced. The novelty of this study suggests that cadres' social roles can be hampered by technical limitations and institutional support. Therefore, role theory must be adapted to community-based social health organizations. Practically, this study proposes regular training, cadre regeneration, and policy support to make cadre roles more effective and sustainable.